Estrategias de lectura y la comprensión lectora en los estudiantes del segundo grado de primaria en la Institución Educativa N° 60756 Claverito, Iquitos 2024 - Yovera Monteza, Sara Yudit (2025)
The purpose of this research is to determine the relationship between the application of reading strategies and reading comprehension in second grade Primary students of the Educational Institution N°60756 Claverito Iquitos 2024. This study has a quantitative design approach. non-experimental, correlational, the population, object of study, consists of all 115 second grade students. To collect data, the observation technique has been used, using an observation guide as an instrument. Regarding the validity of the instrument, these were evaluated by three experts with extensive experience in the area, guaranteeing that the categories and behaviors identified are relevant and appropriate. The results show a Spearman's Rho rating coefficient of 0.746 between reading strategies and reading comprehension, with a bilateral significance of 0.05. In conclusion, the null hypothesis is rejected, since it has been shown that there is a significant relationship between the application of reading strategies and reading comprehension in second grade students of Educational Institution N°60756 Claverito. Iquitos 2024.